Analyzing the Government Social Media Research: A Bibliometric Analysis Using R Biblioshiny. - Nasrullah Nasrullah; Nor Azah Binti Nasrullah Aziz; Noor Hidayah Binti Azmi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study provides a bibliometric analysis of government social media research, focussing on its evolution, important issues, and scholarly contributions. Government social media has developed as an important instrument for increasing openness, communication, and citizen participation. Using the Biblioshiny tool in R, this study uses performance analysis and scientific mapping to detect trends, prominent publications, and research collaborations in the field. The data show a huge growth in scholarly output, with the most articles coming in 2024. China and the United States make the largest contributions, both in terms of volume and worldwide influence. Thematic mapping suggests that research has concentrated on crucial themes such as government-citizen interactions, big data applications, and crisis communication, with rising debates on environmental governance. Co-occurrence analysis revealed two main clusters: one focused on public policy and digital governance, and the other on public health, including COVID-19-related crisis communication. This study highlights the increasingly interdisciplinary nature of government social media research and recommends future paths, particularly in terms of incorporating rising themes such as sustainability and artificial intelligence into governance plans.